2001
DOI: 10.1109/3477.969492
|View full text |Cite
|
Sign up to set email alerts
|

Some novel classifiers designed using prototypes extracted by a new scheme based on self-organizing feature map

Abstract: We propose two new comprehensive schemes for designing prototype-based classifiers. The scheme addresses all major issues (number of prototypes, generation of prototypes, and utilization of the prototypes) involved in the design of a prototype-based classifier. First we use Kohonen's self-organizing feature map (SOFM) algorithm to produce a minimum number (equal to the number of classes) of initial prototypes. Then we use a dynamic prototype generation and tuning algorithm (DYNAGEN) involving merging, splittin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Currently, the SVD-QR with column pivoting algorithm has been proposed to perform rule selection for a parsimonious fuzzy rule-base [17][19]. Unfortunately, some existing studies have shown great sensitivity to the chosen effective matrix rank (MR) values, so that different estimates of the MR often produce dramatically different rule-reduction results [19].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the SVD-QR with column pivoting algorithm has been proposed to perform rule selection for a parsimonious fuzzy rule-base [17][19]. Unfortunately, some existing studies have shown great sensitivity to the chosen effective matrix rank (MR) values, so that different estimates of the MR often produce dramatically different rule-reduction results [19].…”
Section: Introductionmentioning
confidence: 99%
“…The set of gray values corresponding to a pixel in the channel images is used as the feature vector for that pixel. In the first stage a set of labeled prototypes representing the distribution of the training data is generated using a Self-organizing Feature Map (SOFM) [23] based algorithm developed in [24]. The algorithm dynamically decides the number of prototypes based on the training data.…”
Section: Designing the Fuzzy Rule Basementioning
confidence: 99%
“…We use the prototype refinement scheme described in [12,13]. The basic idea behind this refinement algorithm is that a useful prototype, v i should satisfy two criteria:…”
Section: Generation Of Prototypesmentioning
confidence: 99%
“…After a few iterations this algorithm produces a set of adequate number of prototypes that represents the training data much better than the initial one. For details the readers are referred to [12,13]. Now we use these prototypes to generate fuzzy rules that we describe next.…”
Section: Generation Of Prototypesmentioning
confidence: 99%